Development of reduced-fat cheeses with the addition of Agave fructans - Palatnik, Diana Raquel (2016)
Cheeses containing Agave fructans were compared with both full-fat and reduced-fat samples without fructans. Microstructure results showed that the cheeses obtained were very similar to the control samples (without fructans), even the full-fat control sample, demonstrating the texturing role of the carbohydrates. Regarding the composition, a moisture content of 47.96 ± 1.45 and a good protein retention with a low-fat content were found. Therefore, the cheese yield was not adversely affected, and no significant differences were observed in sensory aspects. Considering the health benefits of fructans and their abundance, this development could represent an innovation for dairy industry.